Implementasi Metode Pembelajaran Kewirausahaan Berbasis Kurikulum 2013 Dikelas X Sekolah Menengah Kejuruan Negeri 8 Surakarta - Kurniawati, Ririn Indah, Dr. Djalal Fuadi, M.M (2017)
The purpose in this study to determine: (1) implementation method entrepreneurial learning in the curriculum in 2013, (2) the difference between the methods of teaching in the School SMK Negeri 8 Surakarta method based learning curriculum, 2013, (3) the design implementation of entrepreneurial learning that fits in the curriculum 2013 This research is a qualitative research. The research subject is the teacher of class X SMK Negeri 8 Surakarta. Data collection techniques in this study were interviews, observation and documentation. The validity of the data is done by triangulation is the result of interviews, observation and documentation of results. Data were analyzed using qualitative analysis that includes data reduction, data presentation and conclusion. The research showed that, implementation of the use of learning methods on the subjects of entrepreneurship-based curriculum, 2013. The use of the learning method by combining multiple learning methods. The learning method used in accordance with the curriculum of 2013 and a combination of several methods done by teachers is a contextual approach, lectures, question and answer method, and the method of administration tasks. In addition, teachers also combine contextual approach, lectures, discussion method, and the method of administration tasks. The combination of these methods help students play an active role in learning, creative tasks, classroom atmosphere and learning time more effective, enjoyable learning has been applied to teachers.